Dennis Cutchins, Laurence Raw, and James M. Welsh, editors. The Pedagogy of Adaptation. Scarecrow, 2010. 183 pp. - Çinar, Kaan (Anafora, 2023)
The editors of this collection of papers deserve congratulations for creating a valuable, ground-breaking resource for teaching adaptation at the university level. It represents a timely intervention in adaptation studies, written from the teachers’ point of view. It is ground-breaking in the sense that, at the time of its first publication, it was the first collection dedicated solely to the pedagogy of adaptation. More than anything, it provides explanation on why adaptation studies should be taught as a separate discipline, like film studies are. With contributors from different areas of education within the United States, the collection offers a wide range of essays treating adaptation from different points of view. Starting with the introduction dedicated to the rationale behind teaching adaptation as well as its use in the classroom, The Pedagogy of Adaptation highlights the fact that adaptation is a creative process in which the source text, although it doubtless is an inspiration, ceases to be the focus, along with fidelity, now widely contested as the least relevant of adaptation’s features.